Does Eurosclerosis Matter? Institutional Reform and Labor Market Performance in Central and Eastern Europe - Riboud, Michelle; Sánchez-Páramo, Carolina; Silva-Jáuregui, Carlos (Washington, DC: World Bank, 2013)
This paper examines the labor market dynamics of six CEE countries over the last 10 years, paying special attention to the nature of labor market institutions these countries have adopted and their impact on labor market performance. This paper finds that, compared to EU countries, CEE countries fall in the "middle" of the flexibility scale regarding their employment protection legislation. While the effect of labor market institutions is hard to uncover, it should not be disregarded and they are likely to play an important role in the coming years.